Effect of Patients' Information about Dental Implant Surgery and Treatment Details on Their Pain and Anxiety Level - Jaber Yaghini; Marzieh Kachuie; Narges Naghsh; Zohreh Ashtijoo (Mashhad University of Medical Sciences, 2022)
Introduction: Due to the increasing rate of implant surgery, the present study aimed to determine the effect of informing patients about implant surgery and details of the treatment on their pain and anxiety level.Methods & Materials: In this clinical trial, patients' level of anxiety was initially determined by DAS-R (Dental Anxiety Scale, Revised) questionnaire; thereafter, only the patients with moderate and high levels were included. A total of 22 eligible patients were randomly assigned to two groups. In the study group, the patients were provided with a pamphlet containing basic information and details of operative procedures using, whereas this information was withheld in the control group. The state anxiety (SA) index was used to assess anxiety before and after surgery. Pain during and one week after surgery was assessed using the Visual Analogue scale (VAS) index. Patient satisfaction with the treatment process and the dentist's satisfaction with the convenience of the procedure were determined and compared between the two groups one week after the intervention. Data were analyzed using T-test, Mann-Whitney, paired t-test, and Pearson correlation coefficient. (α=0.05 as a significance level)Results: Based on the results, the two groups did not significantly differ in terms of the mean anxiety before and after surgery, as well as pain during and after the trial (P= 0.49, 0.57, 0.65, 0.51, respectively). Furthermore, dentist convenience (P=0.193) and patient satisfaction (P=0.611) were not significantly different between the groups.Conclusion: As evidenced by the results of this study, there were not any significant differences between the two groups in the assessed variables; nonetheless, the experienced anxiety in both groups was lower than anticipated.